2023
DOI: 10.1007/s10924-023-03018-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoates Production from Cacao Fruit Liquid Residues Using a Native Bacillus megaterium Strain: Preliminary Study

Mabel J. Quintero-Silva,
Silvia J. Suárez-Rodríguez,
Maria A. Gamboa-Suárez
et al.

Abstract: Cacao mucilage exudates (CMEs), byproducts of cacao beans fermentation, are effluents rich in sugars and low-molecular-weight organic acids. In this study, we utilized CMEs to formulate culture media for the biosynthesis of polyhydroxyalkanoates (PHAs) using a native Bacillus megaterium strain (B2). Our investigation followed the adaptation process of B2 to the CMEs-based media, and we closely monitored the development of the microorganism in terms of consumption of acids and sugars. Upon successful adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Within the range of 1000 to 1300 cm −1 , a series of pronounced bands signifies the stretching of the (C-O) bond inherent to the ester group. Importantly, all these spectral features align closely with the standard commercial polyhydroxybutirate (Sigma-Aldrich) (Figure 6); therefore, it is confirmed that the polymeric extract studied is a short chain named polyhydroxybutyrate (PHB) [29,62].…”
Section: Optimization Of Phb Production and Kinetic Studiessupporting
confidence: 69%
See 1 more Smart Citation
“…Within the range of 1000 to 1300 cm −1 , a series of pronounced bands signifies the stretching of the (C-O) bond inherent to the ester group. Importantly, all these spectral features align closely with the standard commercial polyhydroxybutirate (Sigma-Aldrich) (Figure 6); therefore, it is confirmed that the polymeric extract studied is a short chain named polyhydroxybutyrate (PHB) [29,62].…”
Section: Optimization Of Phb Production and Kinetic Studiessupporting
confidence: 69%
“…Additionally, the 3,5-dinitrosalicylic acid (DNS) method was employed to measure sugar concentrations throughout the fermentation time [27]. From the experimental data, the following kinetic parameters were calculated to evaluate growth and PHB production behavior [28][29][30].…”
Section: Analysis Of Bacterial Growth Kineticsmentioning
confidence: 99%
“…For instance, Mozejko-Ciesielska et al [42] reported a highest yield of 0.42 g/L PHA from Halomonas alkaliantarctica using dairy waste as a carbon source. Similarly, Bacillus megaterium was found to secrete 0.98 g PHA/carbon in the presence of cacao fruits residue [43]. In addition, some bacteria, and yeasts (such as Saccharomyces cerevisiae, Candida krusei, Rhodotorula glutinis, Ralstonia eutropha, and Kluyveromyces africans) that utilize polyphosphate complexes in their membrane transport produce low-molecular weight PHB [44,45].…”
Section: Microorganismsmentioning
confidence: 99%